Peningkatan Perilaku Ibu Hamil Melalui Strategi Promosi Kesehatan pada Program ANC di Puskesmas Meral Kabupaten Karimun - Sugiyarningsih Sugiyarningsih; Emy Leonita; Yessi Harnani; Oktavia Dewi; Herniwanti Herniwanti (Jurnal Medika: Medika, 2026)
The behavior of pregnant women in conducting ANC visits remains a challenge in the success of the ANC program. The behavior of pregnant women visiting ANC remains a challenge at the Meral Community Health Center, with coverage of K1 (75.3%), K4 (69.3%), and K6 (64.3%) not meeting the 2024 SPM. This study aims to analyze maternal behavioral factors and health promotion strategies in the 2025 ANC program using a mixed method convergent design. The sample consisted of 130 respondents, 5 stakeholders, and 5 postpartum mothers. Quantitative analysis used multiple logistic regression, while qualitative analysis used triangulation of sources, methods, and data. This study found that K1 was 88.5%, K4 was 85.4%, and K6 was 43.8%. There is a significant relationship between knowledge (p=0.018, POR=6.610, CI: 1.383-31.672), attitude (p=0.002, POR=3.550, CI: 1.574-8.008), and husband's support (p=0.003, POR=3.395, CI: 1.558-8.292) with the behavior of pregnant women. Knowledge is the most dominant factor (POR=6.610). Advocacy is carried out through cross-sector workshops and budget submissions to the Regent/BPKAD, although participation is still low. Cultivating an atmosphere supported by facilities such as air conditioning, priority services, and ultrasound, but educational media are not optimal. Empowerment has been carried out, but human resources are limited. Cross-sector partnerships exist, but coordination and understanding are still weak. Meral Health Center needs to develop community-based innovations integrated with education, family support, and service digitalization